Large scale and integrated platform for digital mass culture of anchorage dependent cells - Kyoung Won Cho (Nature Portfolio, 2019)
Large scale culture of adherent cells would benefit from a platform for continuous monitoring and control of cell growth and culture conditions. Here the authors develop an integrated, smart cell culture platform where cells are grown on multiple layers of thin sensors that can be wirelessly integrated across several incubators.